2004
DOI: 10.1111/j.1365-313x.2004.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

The Etched1 gene of Zea mays (L.) encodes a zinc ribbon protein that belongs to the transcriptionally active chromosome (TAC) of plastids and is similar to the transcription factor TFIIS

Abstract: SummaryEtched1 (et1) is a pleiotropic, recessive mutation of maize that causes ®ssured and cracked mature kernels and virescent seedlings. Microscopic examinations of the et1 phenotype revealed an aberrant plastid development in mutant kernels and mutant leaves. Here, we report on the cloning of the et1 gene by transposon tagging, the localization of the gene product in chloroplasts, and its putative function in the plastid transcriptional apparatus. Several alleles of Mutator (Mu)-induced et1 mutants, the et1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…We could not identify the TAC component ET1, which was recently detected immunologically in maize (Zea mays) (da Costa e Silva et al, 2004). However, it cannot be excluded that this protein is present in the TAC fraction.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We could not identify the TAC component ET1, which was recently detected immunologically in maize (Zea mays) (da Costa e Silva et al, 2004). However, it cannot be excluded that this protein is present in the TAC fraction.…”
Section: Discussionmentioning
confidence: 60%
“…Forty to sixty polypeptides appear to be present in the TAC from chloroplasts, along with two core subunits of PEP and ETCHED1 (ET1) with high homology to the nuclear transcription elongation factor TFSII (Suck et al, 1996;da Costa e Silva et al, 2004). Together with the findings that the ET1-R mutants exhibit quantitative, but no qualitative, differences in TAC activity, it was suggested that ET1 may be involved in plastid mRNA elongation (da Costa e Silva et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The Arabidopsis genome encodes only one putative bacterial-type elongation factor, pTAC13 (At3g09210) containing a KOW domain, which is characteristic for members of the NusG protein family (40). Furthermore, maize ET1, which resembles the eukaryotic elongation factor TFIIS, was identified as a component of the chloroplast transcriptionally active fraction, and plants deficient in ET1 showed an aberrant chloroplast development phenotype and decreased PEP-dependent transcription (21), suggesting that bacterial-type pTAC13 and eukaryotic-type ET1 may be involved in PEP elongation. In this study, we demonstrate that pTAC3 is associated with PEP through transcription initiation and elongation steps, suggesting a possible role for pTAC3 in the regulation of PEP transcription elongation in chloroplasts.…”
Section: % Inputmentioning
confidence: 99%